Youth-led communication for social change: empowerment, citizen media, and cultures of governance in Northern Ghana. Issue 3 (3rd April 2018) - Grauenkaer, Lise; Tufte, Thomas
ABSTRACT: This article critically assesses the possibilities and limitations of strategic communication initiatives to enhance cultures of governance among youth in Northern Ghana. The analysis is embedded within contemporary debates about communication and social change, with particular focus upon dynamics between citizen media development, youth-centred citizen journalism, and processes of community mobilisation and development. Findings suggest that the project has opened up to dynamic, youth-led social change processes, evidenced by the creative, proactive enactment of citizen engagement. Youth changed not only their self-perception around agency and ability to act, but also influenced community development in a variety of ways.